Ethyl biodiesels derived from non-edible oils within the biorefinery concept – Pilot scale production & engine emissions. (August 2017) - Nitièma-Yefanova, Svitlana; Tschamber, Valérie; Richard, Romain; Thiebaud-Roux, Sophie; Bouyssiere, Brice; Bonzi-Coulibaly, Yvonne L.; Nébié, Roger H.C.; Coniglio, Lucie
Abstract: Procedures and operating conditions optimized in laboratory scale for the production of ethyl biodiesels from non-edible vegetable oils (NEVOs) were successfully transferred at pilot scale, with implementation of separation and purification stages. The three NEVOs candidates are Balanites aegyptiaca (BA), Azadirachta indica (AI), and Jatropha curcas (JC), converted into BAEEs, AIEEs and JCEEs respectively via homogeneous catalysis. Quality specifications of the produced biofuels were used to explain pollutant emissions and engine performance observed via a power generator. Under the same conditions, blends of petrodiesel with crude BA or JC oil (50 wt.%) were also investigated. The selected overall methodology "feedstock-conversion-engine" led to the proposal of a sustainable alternative fuel. The candidate NEVO is BA oil to which the proposed alkali route should lead to a low cost biodiesel production process thanks to easy operating conditions, associated with a two-stage procedure (glycerol recycling) and a dry-purification method (rice husk ashes). Glycerol addition should be carried out at ambient temperature to play positively at phenomena occurring in the reacting medium (chemical kinetics, chemical equilibrium, phase equilibrium). Tests on power generator demonstrated that BAEEs led to cleaner combustion than petrodiesel, particularly for the most harmful emissions (light carbonyls and ultrafine particulate matter). Highlights: Three non-edible vegetable oils were converted in ethyl biodiesels. Two-stage ethanolysis (addition of glycerol)/phase-separation/dry-purification. Procedures optimized in lab scale were successfully transferred at pilot scale. Biofuel specifications explained pollutant emissions observed (via power generator). This "feedstock-conversion-engine" methodology led to a sustainable alternative fuel.